Carbon Tax Transformation Strategy in Sustainable Economic Development towards Green Economy in Indonesia - Halizah, Aulia; Furqon, Imahda Khoiri (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This study aims to analyze Indonesia's carbon tax policy in supporting the transformation to a sustainable green economy. The study focuses on reducing carbon emissions as well as increasing state revenue as strategic aspects of carbon tax implementation. Study Design/Methodology/Approach: This research uses a descriptive qualitative approach with a literature study method. Secondary data was obtained from relevant books, journals, news, and websites. Analysis was conducted using the Miles and Huberman method, which includes data collection, data reduction, data presentation, and conclusion drawing. Findings: The results show that carbon tax has the potential to be an effective instrument in supporting green economy transformation by reducing carbon emissions and increasing state revenue. However, this policy faces challenges, such as public resistance, political barriers, and its impact on certain economic sectors. Therefore, strong regulations and supporting policies are needed to ensure effective implementation. Originality/Value: This research contributes to understanding carbon tax policy as a sustainability instrument in Indonesia. Practical implications include the need for a phased and inclusive approach to ensure policy effectiveness and sustainability. Further research can be conducted to explore the impact of carbon tax on strategic economic sectors to ensure optimal implementation.